Dawud, M. Anang Sholikhudin Pendidikan Islam Di SMA Muhammadiyah Dan SMA Ma’arif NU Pandaan: (Studi Komparasi dalam Penanaman Paham ASWAJA). - Dawud Hasan; M. Anang Sholikhudin (Universitas Yudharta Pasuruan, 2019)
abstrack: This research finished to knowing how the Islamic education in elementary high school Muhammadiyah Pandaan, Islamic education in elementary high school Ma’arif NU Pandaan, and comparation of Islamic education from both institutions. This research is quality research. File collection do with using method observation, interview, and documentation. As for analysis file which use this that is file collection, file reduction, file present, conclusion. Research results show that: Islamic education in Muhammadiyah Pandaan about teaching Muhammadiyah, about Muhammadiyah organitation, and Al-Ashri about Arabic language studying, model which use is with strategy lecture and presentation. Islamic education in Ma’arif NU Pandaan is fiqih, qur’an hadits, aqidah akhlak, and SKI, next plus again with subject aswaja/ke-NU-an. model which use is studying with strategy lecture and presentation. Comparation is Muhammadiyah Pandaam superior in time allocation. But, for deepening content in Ma’arif NU Pandaan is superior because can be said PAI be delivered twice past subject ke-NU-an for teen class and for subject PAI alone this.